(untitled) (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Stability analysis of reinforced concrete columns using tables and abacuses often lacks accuracy and leads to more robust structures, with a higher consumption of material (concrete and steel rebars). On the other hand, there are more accurate procedures that derive from detailed models, optimizing the design at the cost of a large number of iterative operations and processes that are not feasible without the use of computers. This paper presents the steps involved in developing a computer code to verify the stability analysis of reinforced concrete columns subjected to axial forces and biaxial bending through computational routines. The computer codes were developed in Matlab, including physical and geometrical nonlinearities, and can be divided into two major parts: (1) characterized by cross section analysis, which is divided into sub-regions for numerical integration, and by varying curvature and neutral axis slope and depth, resistant internal forces and strains are evaluated; (2) a global stability analysis of the structure, where the column is segmented along its height and for each section between the elements a routine evaluates the curvature at equilibrium. The updated deflection is obtained by double curvature integration and provides an additional eccentricity which is added to the initial results into a new iteration. The process is repeated until a convergence criterion is reached or column failure, and thus the final internal forces are computed. The proposed routine results were validated by experimental analysis and finite element simulations with commercial codes Athena and Midas, confirming the validity and efficiency of the present proposal.